2018
DOI: 10.1016/j.bbadis.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyperammonemia alters in opposite ways membrane expression of GluA1 and GluA2 AMPA receptor subunits in cerebellum. Molecular mechanisms involved

Abstract: Hyperammonemia contributes to altered neurotransmission and cognition in patients with hepatic encephalopathy. Hyperammonemia in rats affects differently high- and low-affinity AMPA receptors (AMPARs) in cerebellum. We hypothesized that hyperammonemia would alter differently membrane expression of AMPARs GluA1 and GluA2 subunits by altering its phosphorylation. This work aims were: 1) assess if hyperammonemia alters GluA1 and GluA2 subunits membrane expression in cerebellum and 2) analyze the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The ammonium-containing diet was prepared as described in [33] (but using 25% ammonium acetate) and increased blood ammonia levels around threefold, an increase similar to that found in patients with liver cirrhosis. Rats remain hyperammonemic for long periods of time and reproduce many cognitive and motor alterations present in cirrhotic patients with hepatic encephalopathy and has allowed identifying some underlying mechanisms [7][8][9][34][35][36]. Experiments were performed after 4-5 weeks in the ammonium diet, when the rats are 10-11 weeks old.…”
Section: Model Of Chronic Hyperammonemiamentioning
confidence: 99%
“…The ammonium-containing diet was prepared as described in [33] (but using 25% ammonium acetate) and increased blood ammonia levels around threefold, an increase similar to that found in patients with liver cirrhosis. Rats remain hyperammonemic for long periods of time and reproduce many cognitive and motor alterations present in cirrhotic patients with hepatic encephalopathy and has allowed identifying some underlying mechanisms [7][8][9][34][35][36]. Experiments were performed after 4-5 weeks in the ammonium diet, when the rats are 10-11 weeks old.…”
Section: Model Of Chronic Hyperammonemiamentioning
confidence: 99%
“…The mechanism by which hyperammonemia increases PKC activity in the cerebellum has been already described and is mediated by increased activity of CaMKII which in turn, indirectly, enhances PKC activity [ 2 ]. Increased activity of CaMKII in hyperammonemia is due to increased phosphorylation at the residue Thr286, which is biphasically modulated by calcium concentration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rats with chronic hyperammonemia reproduce the cognitive impairment and motor in-coordination shown by cirrhotic patients with minimal hepatic encephalopathy and are a good model to identify the underlying mechanisms and to test treatments to improve them. Chronic hyperammonemia induces neuroinflammation which alters glutamatergic and GABAergic neurotransmission in cerebellum and hippocampus leading to cognitive and motor impairment [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that rats with chronic hyperammonemia show neuroinflammation in cerebellum and hippocampus, which alters GABAergic and glutamatergic neurotransmission leading to impairment of motor coordination and of spatial and non‐spatial learning and memory (Cabrera‐Pastor et al, ; Cauli eta al., ; Hernández‐Rabaza, Cabrera‐Pastor, Taoro‐Gonzalez, Agusti et al, ; Hernández‐Rabaza, Cabrera‐Pastor, Taoro‐Gonzalez, Malaguarnera ; Taoro‐Gonzalez et al, ). Some of these reports have identified in detail the pathways by which neuroinflammation alters different aspects of neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models have shown that chronic moderate hyperammonemia (HA), similar to that present in cirrhotic patients, is enough to alter cognitive and motor function, because of altered glutamatergic and GABAergic neurotransmission, which, in turn, is because of neuroinflammation (Cabrera‐Pastor et al, ; Cauli et al, ; Hernández‐Rabaza, Cabrera‐Pastor, Taoro‐Gonzalez, Agusti et al, ; Hernández‐Rabaza, Cabrera‐Pastor, Taoro‐Gonzalez, Malaguarnera ; Llansola et al, ; Rodrigo et al, ; Taoro‐González, Arenas, Cabrera‐Pastor, & Felipo, ). Treatment with ibuprofen reduces neuroinflammation in hyperammonemic rats and improves cognitive and motor function (Rodrigo et al, ).…”
Section: Introductionmentioning
confidence: 99%